SORPTION OF COPPER IONS FROM THE WATER SOLUTION BY PARTICLES OF NANOSIZED MAGNETITE - O.D. Linnikov; I.V. Rodina; A.P. Tjutjunnik; V.G. Shevchenko; А.Е. Yermakov; I.V. Medvedeva; А.А. Mysik; M. А. Uimin; Platonv V.V.; Osipov V.V. (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2012)
Sorption of copper ions from water solution by nanosized magnetite performed by three different methods was studied. It was shown that magnetite is effective sorbent for removing copper ions from polluted natural waters and sewage. The obtained data testify that the process of sorption of copper ions by magnetite has chemisorptions character.